Accurate prediction of the properties of materials using the CAM‐B3LYP density functional. Issue 21 (19th May 2021) - Li, Musen; Reimers, Jeffrey R.; Ford, Michael J.; Kobayashi, Rika; Amos, Roger D.
Abstract: Density functionals with asymptotic corrections to the long‐range potential provide entry‐level methods for calculations on molecules that can sustain charge transfer, but similar applications in materials science are rare. We describe an implementation of the CAM‐B3LYP range‐separated functional within the Vienna Ab‐initio Simulation Package (VASP) framework, together with its analytical functional derivatives. Results obtained for eight representative materials: aluminum, diamond, graphene, silicon, NaCl, MgO, 2D h‐BN, and 3D h‐BN, indicate that CAM‐B3LYP predictions embody mean‐absolute deviations (MAD) compared to HSE06 that are reduced by a factor of six for lattice parameters, four for quasiparticle band gaps, three for the lowest optical excitation energies, and six for exciton binding energies. Further, CAM‐B3LYP appears competitive compared to ab initio G0 W0 and Bethe‐Salpeter equation approaches. The CAM‐B3LYP implementation in VASP was verified by comparison of optimized geometries and reaction energies for isolated molecules taken from the ACCDB database, evaluated in large periodic unit cells, to analogous results obtained using Gaussian basis sets. Using standard GW pseudopotentials and energy cutoffs for the plane‐wave calculations and the aug‐cc‐pV5Z basis set for the atomic‐basis ones, the MAD in energy for 1738 chemical reactions was 0.34 kcal mol −1, while for 480 unique bond lengths this was 0.0036 Å; these values reduced to 0.28 kcal mol −1 (largest error 0.94 kcal mol −1 ) and 0.0009 Å by increasing the plane‐wave cutoff energy to 850 eV. Abstract :